1997
DOI: 10.1073/pnas.94.11.5961
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis thaliana ethylene-responsive element binding protein (AtEBP), an ethylene-inducible, GCC box DNA-binding protein interacts with an ocs element binding protein

Abstract: Ocs elements are a group of promoter sequences required for the expression of both pathogen genes in infected plants and plant defense genes. Genes for ocs element binding factors (OBFs), belonging to a specific class of basic-region leucine zipper (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
247
0
3

Year Published

1999
1999
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 328 publications
(264 citation statements)
references
References 59 publications
6
247
0
3
Order By: Relevance
“…6, K-O). AtERF1b, AtERF2, and AtEBP1 are ET-responsive activators of GCC-box genes (Bü ttner and Singh, 1997;Fujimoto et al, 2000).The weakly up-regulated AtRCD1 modulates ET, abscisic acid (ABA), and methyl-JA responses (Ahlfors et al, 2004). Two uncharacterized putative TFs, At5g07580 and At5g25190, annotated as possibly involved in ET signaling, are down-regulated (Supplemental Table XIII), one yields no significant signal.…”
Section: Ethylenementioning
confidence: 99%
“…6, K-O). AtERF1b, AtERF2, and AtEBP1 are ET-responsive activators of GCC-box genes (Bü ttner and Singh, 1997;Fujimoto et al, 2000).The weakly up-regulated AtRCD1 modulates ET, abscisic acid (ABA), and methyl-JA responses (Ahlfors et al, 2004). Two uncharacterized putative TFs, At5g07580 and At5g25190, annotated as possibly involved in ET signaling, are down-regulated (Supplemental Table XIII), one yields no significant signal.…”
Section: Ethylenementioning
confidence: 99%
“…Recently, it has been shown that DELLAs counteract the effect of ethylene during apical hook development by inhibiting the activity of ETHYLENE INSENSITIVE3 (EIN3) through physical interaction, providing a mechanism for the coregulation of this process by GAs and ethylene . It was previously shown that RAP2.3 expression is induced by ethylene (Büttner and Singh, 1997). Significantly, EIN3 binds in vivo to the RAP2.3 promoter (Chang et al, 2013) and activates its expression in etiolated seedlings (Fig.…”
Section: Dellas Prevent the Binding Of Rap23 To The Promoter Of Its mentioning
confidence: 78%
“…RAP2.3 belongs to the group VII ERFs of the AP2/EREBP superfamily (Nakano et al, 2006). Given that (1) no member of this family has been previously reported as a DELLA interactor (Locascio et al, 2013b) and (2) it participates in the ethylene signaling cascade (Büttner and Singh, 1997), which is known to control apical hook formation (Guzmán and Ecker, 1990), we decided to investigate the functional connection between GAI and RAP2.3.…”
Section: Identified Della Interactors Affect Ga Responsesmentioning
confidence: 99%
See 1 more Smart Citation
“…22 In D. japonica callus culture, exogenous ethylene elevated the chitinase activity. 23 In addition, jasmonic acid (JA) acts as signal that promotes defense system in plant and regulates the plant's responses to wounding. The expression of the SafchiA from C. sativus was affected by JA and wounding directly, but not by ethylene, abscissic acid or salicylic acid (SA).…”
Section: Discussionmentioning
confidence: 99%